Study manual for the Test of Essential Academic Skills (TEAS) : reading, mathematics, science, and English and language usage / Amanda Wolkowitz - Wolkowitz, Amanda
The TEAS is a 170-item, four-option, multiple-choice examination offered in both paper and computer-administered formats. This guide has been designed to parallel the proctored TEAS. It contains instructional material for each of the four subject areas addressed, practices problems with explanatory answer keys, and two comprehensive practice tests with explanatory answer keys.